Challenging the new blue deal by embedding interactions with the non-humans in the offshore renewable energy development - Boemare, Catherine (Frontiers in Marine Science, 2023)
This paper is challenging the new blue deal outlining the need for a change in the expectative. OWF are not only a climate-friendly way of producing electricity but also a shifting paradigm unique opportunity, acknowledging the increasing presence of anthropogenic infrastructure in the marine environment and seeing them as the place for re-creating relations with non-humans and work with them. We give some ideas that could ground a research program pairing both positive and negative aspects of OWF and study the conditions of realization of mutual beneficial relationship coming from the “mosaic of open-ended assemblages of entangled ways of life”.